Influence of natal habitat preference on habitat selection during extra‐home range movements in a large ungulate. Issue 2 (3rd February 2023) - Hooven, Nathan D.; Springer, Matthew T.; Nielsen, Clayton K.; Schauber, Eric M.
Abstract: Natal habitat preference induction (NHPI) occurs when animals exhibit a preference for new habitat that is similar to that which they experienced in their natal environment, potentially leading to post‐dispersal success. While the study of NHPI is typically focused on post‐settlement home ranges, we investigated how this behavior may manifest during extra‐home range movements (EHRMs), both to identify exploratory prospecting behavior and assess how natal habitat cues may influence path selection before settlement. We analyzed GPS collar relocation data collected during 79 EHRMs made by 34 juvenile and subadult white‐tailed deer ( Odocoileus virginianus ) across an agricultural landscape with highly fragmented forests in Illinois, USA. We developed a workflow to measure multidimensional natal habitat dissimilarity for each EHRM relocation and fit step‐selection functions to evaluate whether natal habitat similarity explained habitat selection along movement paths. Across seasons, selection for natal habitat similarity was generally weak during excursive movements, but strong during dispersals, indicating that NHPI is manifested in dispersal habitat selection in this study system and bolstering the hypothesis that excursive movements differ functionally from dispersal. Our approach for extending the NHPI hypothesis to behavior during EHRMs can be applied to a variety of taxa and can expand our understanding of how individual behavioral variation and early life experience may shape connectivity and resistance across landscapes. Abstract : Dispersing animals often rely upon cues from their early environment to maximize their post‐dispersal success. We found that white‐tailed deer select for familiar habitat along dispersal paths, suggesting important implications for animal movement and landscape connectivity.